Qirā’at In Tafsīr Al-Jalālain Book; A Descriptive Study of Ṣighat Wafi Qira`Atin in the 30th Juz. - Ahmad Farih; Abdullah Khoirur Rofiq; Alvian Bhakti Pamungkas (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The differences in dialects owned by the Arabs result in differences in the way the Qur'an is recited or often known as differences in qirā'at. When Muslims began to develop, the study of religious sciences also developed, such as the study of the verses of the Qur'an to be interpreted, when interpreting the verses of the Qur'an, many mufassirs have attention to differences in qirā' at, such as in the book of Tafsir al-Jalâlain. Problems arise when encountering the phrase wa fī qirā'atin in the book of Tafsīr al-Jalālain because it does not explain who is referred to in the phrase so that it does not know the status of the validity of the qirā'at, whether it is mutawatir, ahad or even syadz. This paper uses library research, while the data collection technique used is document review technique, then analyzed using descriptive analytical method, with a deductive mindset, namely looking for lafadz wa fī qirā'atin in the book of Tafsīr al-Jalālain in 30th Juz then looking for the status of qira`ah. The benefits of this research include introducing the imams of qirā'at and their positions, especially those contained in the memorization of wa fī qirā'atin in the book of Tafsīr al-Jalālain in juz 30. As for the results of this research paper, the author found the phrase wa fī qirā'atin in the book of Tafsīr al-Jalālain in the 30th Juz. imams who contained in it are imams of qira`ah arba`ah asyrah. Meanwhile, when viewed from the status of the authenticityof the qirā'at, it has a mutawatir status because in each lafadz it contains the name of one or more of the imams of the qira`ah sab`ah.